Design of eSCM and eCRM Integration in Extraprise Scope: Case of Nurafni Collection - Rahmadani , Muhammad Addy; Harahap , Rahmayani; Syafitri, Ika Nur; Ilham , M.; Istambul, Muhammad Rozahi (International Journal of Psychosocial Rehabilitation, 2020)
Opportunities in the utilization of information technology to gain an edge in the business competition should be the main focus of every organization. The presence of the ecosystem in managing business processes, resulting in a supply chain relationship between one company with other companies that make up an enterprise. The case study conducted in the organization Nurafni Collection as a place of business process which initially still performs business transactions in a manual to be used as research in applying electronic supply chain management (eSCM) which is combined with electronic Customer Relationship Management (eCRM). So can be seen the results holistically, then assisted using a modeling archimate.